Adaptive loading with Principal Component Filter Banks in MIMO MultiCarrier Modulation System. (20th November 2009) - Sheeba, V.S.; Elias, Elizabeth
We discuss adaptive loading scheme in wireless MultiCarrier Modulation Systems (MCMS), using Variable-Rate Variable-Power (VRVP), coded, M-ary quadrature amplitude modulation. The Principal Component Filter Bank (PCFB), which is adapted to the channel characteristics, is used for converting the wideband channel into narrow-band sub-channels. PCFB-based adaptive scheme gives better performance in terms of spectral efficiency and bit error rate, compared with the conventional scheme in MCMS. The main advantage of using PCFB in adaptive loading is that constellation size need not be varied frequently on each subcarrier depending on the channel Signal-to-Noise Ratio (SNR). We extend this idea to Multi-Input Multi-Output (MIMO) systems.